Specialization in Same-Sex and Different-Sex Couples - Thomas Hofmarcher; Erik Plug (Institute of Labor Economics (IZA), 2021)
We examine time allocation decisions in same-sex and different-sex couples from a Beckerian comparative advantage perspective. In particular, we estimate the comparative advantage relationship between time spent on either market or household activities and a dummy for being the highest earner in a couple on samples of same-sex and different-sex couples. Using the American Time Use Survey (ATUS), we find that same-sex couples specialize not as much as different-sex couples. We argue that these specialization differences are driven by the most traditional different-sex couples. Without married couples with wives at home taking care of children and husbands working outside the home, which represent at most 20 percent of all different-sex couples, we find that the highest earner in a couple spends 80 minutes more per day on market work and 40 minutes less per day on household work, regardless their sexual orientation. We therefore conclude that, from a comparative advantage perspective, most same-sex and different-sex couples specialize equally.
Keywords: D13; J15; J22; 330; time allocation; household work; market work; same-sex couples; different-sex couples; comparative advantage